The Image of Java and Its People in Emilie’s Eyes Under the Perspective of New Historicism - Sentana, Yuli Mahmudah; Felayati, Safrina Arifiani; Blace, Léa (Center of Language Development, Institut Agama Islam Negeri Madura, 2023)
Emilie Java 1904 by Catherine Van Moppès is a French novel that portrays Indonesia's portrait in Java in 1904, a century of Dutch colonialism in Indonesia. This novel describes Indonesian colonialism through the third lens, a narration from a French person's point of view. This research aims to identify the historiography of Java in 1904, where the Dutch carried out deep colonialism using a new historicism perspective. The qualitative descriptive method was used. The data involved words, phrases, and sentences containing Javanese historiography in the novel. This study found that 1) the Javanese people are friendly, embrace Islam, and have solid ancient beliefs. The nature of Javanese men who still despise women is also reviewed; 2) From the European perspective, Java's conditions are described as exotic and beautiful but chaotic and dangerous; 3) Colonialism is also seen from a neutral side by writing that shows the negative side of priyayi and the arbitrary attitude of the Dutch toward the natives. This novel implies that the Javanese were civilized before the Dutch came, which contradicts the primary purpose of Westerners coming to the East. Otherwise, she also showed the negative and positive side of Java and its people toward the Dutch.